Preferences for Stock Characteristics as Revealed by Mutual Fund Portfolio Holdings - Falkenstein, Eric (Journal of Finance, 1996)
This investigation of the cross-section of mutual fund equity holdings for the years 1991 and 1992 shows that mutual funds have a significant preference towards firms with high visibility and low transaction costs, and are averse to stocks with low idiosyncratic volatility. These findings are relevant to theories concerning investor recognition, a potential agency problem in mutual funds, tests of trend-following and herd behavior by mutual funds, and corporate finance.